Pengaruh Suhu dan Waktu Pengeringan Pada Bioplastik dari Pati Jagung Terhadap Waktu Biodegradasi - Mirra Amanda Syamsyyah; Myra Wardati Sari; Cengristitama Cengristitama; Lulu Nurdini (Eksergi, 2023)
The disposal plastic waste into the environtment is an important issue due to the natureof the origin of plastics that are difficult to decomposes naturally. Therefore, efforts are made to accelerate the degradation time by using natural polymers. Corn is one of the easily found sources of starch. Starch is one of the natural polymres that can be used for the manufacture of biodegradable plastics (bioplastics) because it is easily degradable, readily available and affordable but has shortcomings in mechanical properties and water absorption ability.The purpose of this study was to observe the effect of temperature variations 60; 70; 80 and 90°C with a drying time of 1; 2; 3 and 4 hours of biodegradation time. From this study, the best results were found at a temperature of 60°C with a drying time of 1 hour which obtained a degradation time of 5 days; average thickness 0.12 mm – 0.30 mm; the overall average water absorption is 4.04% and the average water resistance is 95.99%; tensile strength of 5.69 MPa and 5.54 MPa; elongation at break of 4% and 1.6%.